Diagnosis and antibiotic treatment of acute otitis media: report from International Primary Care Network. Issue 6724 (3rd March 1990) - Froom, J; Culpepper, L; Grob, P; Bartelds, A; Bowers, P; Bridges-Webb, C; Grava-Gubins, I; Green, L; Lion, J; Somaini, B
Abstract : STUDY OBJECTIVE--The relation between a history of disorders suggestive of acute otitis media, symptoms, and findings of an examination of the tympanic membrane and doctors' certainty of diagnosis. Also, to examine differences in prescribing habits for acute otitis media among doctors from different countries. DESIGN--Questionnaires were completed by participating doctors for a maximum of 15 consecutive patients presenting with presumed acute otitis media. SETTING--General practices in Australia, Belgium, Great Britain, Israel, The Netherlands, New Zealand, Canada, Switzerland, and the United States. PATIENTS--3660 Children divided into the three age groups 0-12 months, 13-30 months, and greater than or equal to 31 months. MAIN OUTCOME MEASURES--General practitioners' responses to questions on their diagnostic certainty and resolution of patients' symptoms after two months. RESULTS--The diagnostic certainty in patients aged 0-12 months was 58.0%. This increased to 66.0% in those aged 13-30 months and 73.3% in those aged greater than or equal to 31 months. In all age groups diagnostic certainty was positively associated with the finding of a tympanic membrane that was discharging pus or bulging. Redness of the membrane and pain were also associated with certainty in patients aged 13-30 months, and a history of decreased hearing or recent upper respiratory infection was positively associated in patients aged greater than or equal to 31 months. The proportion of patients prescribed antibiotics varied greatly among the countries, from 31.2% in The Netherlands to 98.2% in both Australia and New Zealand, as did the duration of treatment. Patients who did not take antibiotics had a higher rate of recovery than those who did; the rate of recovery did not differ between different types of antibiotic. CONCLUSIONS--Doctors' certainty of diagnosis of acute otitis media was linked to patient's age. Improved criteria or techniques for diagnosing acute otitis media, especially in very young children, need to be developed. Antibiotic treatment did not improve the rate of recovery of patients in this study.